2020
DOI: 10.1016/j.vas.2020.100132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water restriction on feed intake, digestion, and energy utilization by mature female St. Croix sheep

Abstract: Highlights Ruminant livestock are frequently exposed to stress factors impacted by climate. A 50% water restriction increased digestibility in mature St. Croix sheep. But, ME intake did not differ because of numerical differences in feed intake. There is a variable relationship between BW and water restriction. An effect of water restriction on digestibility may influence BW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…In accordance, feed intake was slightly decreased by water restriction in this study [ 21 ]. However, generally greater levels of cholesterol and triglycerides in period three than earlier could relate to increased digestibility and BW during water restriction [ 21 , 26 ]. It was also reported that complete water restriction for 4 d reduced thyroid hormone concentration in the blood of sheep [ 22 ], which has been negatively related to blood cholesterol and triglyceride levels [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, feed intake was slightly decreased by water restriction in this study [ 21 ]. However, generally greater levels of cholesterol and triglycerides in period three than earlier could relate to increased digestibility and BW during water restriction [ 21 , 26 ]. It was also reported that complete water restriction for 4 d reduced thyroid hormone concentration in the blood of sheep [ 22 ], which has been negatively related to blood cholesterol and triglyceride levels [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the most common breeds of hair sheep in the USA, Dorper, Katahdin, and St. Croix, have been evaluated for resilience to stress factors that are expected to increase in importance with changing climate [ 21 , 26 , 27 , 28 , 29 , 30 ]. The selection of animals of these breeds in regions of the USA where they were first introduced over several decades may have affected some of their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration is positively correlated with heat stress, heat stress causes increased body temperatures which stimulates physiological responses like sweating and vasodilation to increase heat dissipation in the environment ( Akerman et al, 2016 ), which in turn increases water consumption by an animal. Notwithstanding the impacts of water stress on animal production, some studies have suggested that ruminants have developed mechanisms of coping with the negative effects of both heat and water stress ( Hussein et al, 2020 ).…”
Section: Potential Climate Change Variables Impacting On Sheep Geneti...mentioning
confidence: 99%
“…It indicated significant difference in the nutritional status of animals among the treatment groups. Digestibility of a feed is not a fixed trait but is modified by various factors such as the level of feed intake, fodder variety (Avornyo, 2020) water consumption (Hussein et al, 2020), age and state of animal production.…”
Section: Intake and Digestibilitymentioning
confidence: 99%